Calorie elasticities with income dynamics: Evidence from the literature - De Zhou; Xiaohua Yu (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2014)
This paper proposes a finite mixture model (FMM) to model the behavioral transition of calorie consumption with an assumption that nutrition consumption is a mixture of two different behavioral stages: a poor stage and an affluent stage. Based on 387 calorie-income elasticities collected from 90 primary studies, our results identify that the threshold income for calorie demand transition is 459.8 USD in 2012 prices (PPP). It implies that the transitional threshold for calorie consumption is 1.26 dollar/day, which is slightly lower than the World Bank poverty line (1.25 dollar/day in 2005 PPP prices).
Keywords: D12; 330; nutrition transition; calorie consumption; income elasticity; finite mixture model